Konsep Pendidikan Karakter Berbasis Pendidikan Agama - Hafidhuddin, Didin (Ta’dibuna: Jurnal Pendidikan Islam, 2018)
The objective of every education in Islam is that it helps molding good character (akhlaq) of the educated, equips rum to face life here in this world and hereafter simultaneously, prepares him to keep and maintain the spirit of perusing knowledge, encourages him to seek and make new discovery (intellectual curiosity), furnish him with skill that suit his talent and ability, teach them to have a sense of responsibility in their life as a servant of Allah and as social being, and invite them to reflect and understand the wisdom behind the creation of universe and make use of it.